Parametrical design and optimization of a reverse circulation drill bit for dust control - Fan, Liming; Li, Zhilin; Luo, Yongjiang (Frontiers in Built Environment, 2024)
Reverse circulation down-the-hole air hammer drilling (RC-DTH) method renowned for their efficiency in hard rock formations and exceptional dust control performance. Which presents opportunities for cost-saving, efficiency improvement, energy conservation, and environmental protection. And reverse circulation drill bits are critical components of this method. This study focused on the air reverse circulation regime, investigating various geometric parameters of RC drill bits through computational and experimental methods to enhance its dust control performance. Results indicate that increasing the layers of suction nozzles, enlarging the diameters of suction and mixing nozzles, and optimizing the input airflow rate can effectively channel airflow towards the central passage of the drill tool. Consequently, this optimization significantly improves the dust control performance of RC drill bits. Conversely, increases in flushing nozzle diameter and alterations in suction nozzle location have detrimental effects on the dust control capability of RC drill bits. Field tests were conducted at the Yuan Jiacun iron mine, affiliated with Taiyuan Iron & Steel (Group) CO., LTD. Field tests demonstrate that the optimized RC drill bit exhibits excellent dust performance.